Airway Pressure Release Ventilation Mode Improves Circulatory and Respiratory Function in Patients After Cardiopulmonary Bypass, a Randomized Trial - Ge, Huiqing; Lin, Ling; Xu, Ying; Xu, Peifeng; Duan, Kailiang; Pan, Qing; Ying, Kejing (Frontiers in Physiology, 2021)
Importance: Postoperative pulmonary complications and cardiovascular complications are major causes of morbidity, mortality and resource utilization in cardiac surgery patients. Objectives: To investigate the effects of airway pressure release ventilation (APRV) on respiration and hemodynamics in post cardiac surgery patients. Main outcomes and measures: A single-center randomized control trial was performed. In total, 138 patients undergoing cardiopulmonary bypass were prospectively screened. Ultimately 39 patients met the inclusion criteria and were randomized into two groups: 19 patients were managed with pressure control ventilation (PCV) and 20 patients were managed with APRV. Respiratory mechanics after 4 hours, hemodynamics within the first day, and chest radiograph score and blood gases within the first three days were recorded and compared. Results: A higher cardiac index (3.1 ± 0.7 vs. 2.8 ± 0.8 L·min−1·m2; p < 0.05), and shock volume index (35.4 ± 9.2 vs. 33.1 ± 9.7 ml·m−2; p < 0.05) were also observed in the APRV group after 4 hours as well as within the first day (p<0.05). Compared to the PCV group, the PaO2/FiO2 was significantly higher after 4 hours in patients of APRV group (340 ± 97 vs. 301 ± 82, p < 0.05) and within the first three days (p < 0.05) in patients in the APRV group. Chest radiograph score revealed less overall lung injury in the APRV group (p < 0.001). Conclusions and relevance: Compared to PCV, APRV may be associated with increased cardiac output improved oxygenation, and decreased lung injury in postoperative cardiac surgery patients.